Urinary bisphenol A and pubertal development in Chinese school-aged girls: a cross-sectional study - Maohua Miao; Ziliang Wang; Xiaoqin Liu; Hong Liang; Zhijun Zhou; Hui Tan; Wei Yuan; De-Kun Li (BMC, 2017)
Abstract Background Animal studies suggest that bisphenol A (BPA) may perturb pubertal development in females. However, evidence from human studies is limited. Methods This was a cross-sectional study to investigate the association between BPA exposure and pubertal development in school-aged girls. A total of 655 girls aged 9-18 years were selected from three schools in Shanghai, from May to June 2011. We collected one single spot urine sample from each girl. Urine BPA concentrations were measured by modified high-performance liquid chromatography and categorized according to LOD and the median of those above LOD. Pubertal development status was assessed by using Tanner staging, and age at menarche was collected as a milestone for mid-puberty. Modified Poisson regression was used to estimate adjusted prevalence ratios (PRs) and 95% confidence intervals (CIs). Results After adjustment for potential confounders, girls with detected BPA were more likely to have delayed menarche, a mid-puberty event, compared with girls with undetectable BPA; the prevalence ratios (PR) were 0.73 (0.56, 0.95) for those with moderate BPA(LOD-median) and 0.72 (0.52, 0.99) for those with high BPA(>median), respectively. Girls aged 9-12 years with detected BPA were more likely to have reached pubic hair stage 2, the indicator of pubarche; while among girls aged >15 years, those with detected BPA were less likely to have reached pubic hair stage 5, the late stage of pubic hair development. Conclusions BPA exposure was associated with alterations in the timing of pubertal development. Results in the present study should be interpreted with caution because of its cross-sectional nature and the limited sample size in each age group.